Liquiritin improves macrophage degradation of engulfed tumour cells by promoting the formation of phagolysosomes via NOX2/gp91phox - Caiyi Yang; Kehan Chen; Yunliang Chen; Xuting Xie; Pengcheng Li; Meng Zhao; Junjie Liang; Xueqian Xie; Xiaoyun Chen; Yanping Cai; Bo Xu; Qing Wang; et al. (Journal of Pharmaceutical Analysis)
The incomplete degradation of tumour cells by macrophages (Mϕ) is a contributing factor to tumour progression and metastasis, and the degradation function of Mϕ is mediated through phagosomes and lysosomes. In our preliminary experiments, we found that overactivation of NADPH oxidase 2 (NOX2) reduced the ability of Mϕ to degrade engulfed tumour cells. Above this, we screened out liquiritin from Glycyrrhiza uralensis Fisch, which can significantly inhibit NOX2 activity and inhibit tumours, to elucidate that suppressing NOX2 can enhance the ability of Mϕ to degrade tumour cells. We found that the tumour environment could activate the NOX2 activity in Mϕ phagosomes, causing Mϕ to produce excessive reactive oxygen species (ROS), thus prohibiting the formation of phagolysosomes before degradation. Conversely, inhibiting NOX2 in Mϕ by liquiritin can reduce ROS and promote phagosome-lysosome fusion, therefore improving the enzymatic degradation of tumour cells after phagocytosis, and subsequently promote T cell activity by presenting antigens. We further confirmed that liquiritin down-regulated the expression of the NOX2 specific membrane component protein gp91 phox, blocking its binding to the NOX2 cytoplasmic component proteins p67 phox and p47 phox, thereby inhibiting the activity of NOX2. This study elucidates the specific mechanism by which Mϕ cannot degrade tumour cells after phagocytosis, and indicates that liquiritin can promote the ability of Mϕ to degrade tumour cells by suppressing NOX2.